2007
DOI: 10.1007/s00221-007-1164-0
|View full text |Cite
|
Sign up to set email alerts
|

Coherent intracerebral brain oscillations during learned continuous tracking movements

Abstract: The aim of the present study was to assess changes in electroencephalogram (EEG) phase locking between fronto-parietal areas, including the frontal and parietal motor areas, during audiomotor learning of continuous tracking movements. Subjects learned to turn a steering wheel according to a given trajectory in order to minimise the discrepancy between a changing foreground stimulus (controllable by the subjects) and a constant background stimulus. The results of the present study show that increasing practice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…In our recent work, we found activation in early learning that overlapped with that associated with SWM for young adults (Anguera et al, 2010). This pattern is similar to other studies of visuomotor transformations (Blum et al, 2007, 2008). In contrast, we found that a failure to engage SWM networks during visuomotor adaptation by older adults was associated with learning deficits (Anguera et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…In our recent work, we found activation in early learning that overlapped with that associated with SWM for young adults (Anguera et al, 2010). This pattern is similar to other studies of visuomotor transformations (Blum et al, 2007, 2008). In contrast, we found that a failure to engage SWM networks during visuomotor adaptation by older adults was associated with learning deficits (Anguera et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with previous research of our group [29,30], task-related power was calculated for five individually defined frequency bands. The four individual frequency bands covering the alpha and beta ranges were defined using the following procedure: At first, the individual alpha peak was determined for each subject: The power spectra pooled over the two lateral EOIs were compared between the movement and the resting periods (averaged across the whole experiment) and the individual alpha peak (iAP) was defined as the frequency showing the strongest difference.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were asked to practice a bimanual visuomotor tracking paradigm, which has been used in previous studies of our group [29]. In order to improve task-performance, participants had to learn to bimanually move a steering wheel according to a predefined movement pattern to minimize the difference between a changing foreground stimulus and a constant background stimulus.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies, applying different methods, have evaluated brain function during learning and executing motor skills (Blum, Lutz, Pascual-Marqui, Murer, & Ja¨ncke, 2008;Willingham, 1999), and one of the most common of these has involved variations in brainwaves. Electroencephalography (EEG) is a method for recording electrical activity of the brain; EEG reflects a person's psychophysiological state during performance because brainwaves can be sensitive to changes in attention and cognitive demands (Smith, McEvoy, & Gevins, 1999).…”
Section: Introductionmentioning
confidence: 99%